Chapter Irreversible electroporation in pancreatic cancer - Holzgang, Melanie (InTechOpen, 2018)
Pancreatic cancer is the deadliest of the gastrointestinal tract with 5-year survival rates of less than 5%. Given common asymptomatic early disease course, most patients (50%) present with an already metastatic disease, while only 20% can undergo potentially curative resection. The remaining 30% present with locally advanced disease, defined as extended vascular encasement, where the risk of surgical therapy often outweighs its benefits. Traditional thermal local ablative modalities (RFA, MWA, or cryotherapy) have the disadvantage that they are not applicable in proximity to vital vascular structures, which are abundant in the peripancreatic region. Irreversible electroporation (IRE) is an emerging non-thermal alternative that induces apoptosis of tumor cells by the delivery of short repetitive impulses of high-voltage electric current. Given its mostly non-thermal modality, IRE is not hampered by a heat-sink effect and is applicable with little risk around vascular structures, bile and pancreatic ducts. Recent research suggests that local tumor destruction through IRE improves overall survival, progression-free survival and quality of life in patients with locally advanced pancreatic cancer.